Psychometric study of the Mentallypro Scale for the evaluation of exposure to psychological risk factors in the work environment. - Guardia i Olmos, Joan; Peró-Cebollero, Maribel; Carbó-Carreté, Maria; Cañete-Massé, Cristina (Anales de Psicología / Annals of Psychology, 2024)
Background: This paper presents the new Mentallypro Scale for the Assessment of Exposure to Psychological Risk Factors in the Work Environment. Its appearance comes to solve some of the limitations of the current scales that either do not present updated scales or have mismatches to the current work environment. Method: 6881 workers distributed in 11 different sectors of activity completed the final scale, obtained after a test scale. The final scale consists of 56 ipsative items presented in blocks of four, so that the respondent can order them based on their highest to lowest identification with the item’s content. The items define 14 factors and standardized scores have been obtained for each factor and sector of activity based on the distribution of Intellectual Quotients (IQ) [μ = 100 and σ = 15]. Results: All the psychometric indicators show a high degree of validity and reliability. Additionally, scores have been corrected for Age and Gender to remove the item differential effect. Conclusions: The scale presented meets the psychometric requirements and resolves the limitations of other scales in terms of ease, speed, and utility in the work environment.